Perencanaan Produksi Tenun Ikat Petra Clik Di Kota Kupang - Abineno, Nidya; Nidya Patty Noverisa Abineno; Yoseba Pulinggomang; Erna Eryani Giri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The research entitled Production Planning of Tenun Ikat Petra Cilik in Kupang City aims to find out and explain the production planning of Tenun Ikat Petra Cilik in Kupang City. Data collection techniques in this study are observation, interviews, documentation and questionnaires. While data analysis techniques use forecasting and Break Event Point (BEP).The results showed that the amount of sales forecast for sarongs at Tenun Ikat Petra Cilik in 2024 was 174 sheets, in 2025 as many as 202 sheets and 2026 as many as 219 sheets. For blankets in 2024 as many as 107 pieces, in 2025 as many as 110 pieces and in 2026 as many as 113 pieces. For sashes on Tenun Ikat Petra Cilik shows that in 2024 there were 199 sheets, in 2025 there were 201 sheets and in 2026 there were 204 sheets. The results of the Break Event Point (BEP) analysis show that if Tenun Ikat Petra Cilik in Kupang City produces 101 pieces of sarong or Rp.152,000,000, for blankets producing 162 pieces or Rp. 162,857,142 and sling producing 1,380 pieces or Rp.411.940.298, then Tenun Ikat Petra Cilik will not make a profit or not suffer a loss because at that point Tenun Ikat Petra Cilik is in a state of basic return. And if the company produces below the BEP point, the company will experience a loss, and vice versa if the company produces above the BEP point, the company will experience a profit. Based on the results of the study, it is recommended that it be taken into consideration for the company in relation to making decisions on determining the number of orders and good planning for the supply of woven raw materials in order to smooth the production process in the company. And for the company, Tenun Ikat Petra Cilik needs to make a production plan or the amount of production to be produced appropriately in order to provide maximum profit. Produksi Keywords :Planning,Production